Intervention Effects on Foster Preschoolers’ Attachment-Related Behaviors From a Randomized Trial - Fisher, Philip A. (2007)
This study examines change in attachment-related behaviors among foster preschoolers participating in a randomized trial of the Multidimensional Treatment Foster Care Program for Preschoolers (MTFC-P). Measures of secure, resistant, and avoidant behaviors were collected using a caregiver-report diary at 3-month intervals during the 12 months following a new foster placement. Children randomly assigned to the MTFC-P intervention condition (n = 57) showed significant increases in secure behavior and significant decreases in avoidant behavior relative to children assigned to a regular foster care condition (n = 60). Both groups showed significant decreases in resistant behavior over time. Analyses also revealed a significant interaction between treatment condition and age at first foster placement on change in secure behavior. Results are discussed in terms of the importance of early intervention and prevention services for foster preschoolers.